2007
DOI: 10.1063/1.2432380
|View full text |Cite
|
Sign up to set email alerts
|

The effect of order and dose of H and He sequential implantation on defect formation and evolution in silicon

Abstract: In this paper we study the effect of the order and dose of H and He sequential implantation on H interaction with Si lattice defects. We use systematic infrared absorption measurements to investigate the evolution of hydrogenated point defects complexes during isothermal annealing. This analysis combined with the electron microscopy data led to the identification of the infrared absorption modes corresponding to the formation of the partially amorphized layer. The obtained results provide an important input fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Summarizing the state of the art, 5,6,[11][12][13][14] when coimplanting helium, it is generally thought that helium incorporates and over-pressurizes the hydrogen platelets during annealing and thus promotes their mechanical coalescence and the formation of blisters. It has been reported that this synergetic interaction was not so effective when He was implanted deeper than H and after H, likely because this second implant destroys the H related complexes formed after H implantation, while these complexes are thought to be the precursors of platelets and blisters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Summarizing the state of the art, 5,6,[11][12][13][14] when coimplanting helium, it is generally thought that helium incorporates and over-pressurizes the hydrogen platelets during annealing and thus promotes their mechanical coalescence and the formation of blisters. It has been reported that this synergetic interaction was not so effective when He was implanted deeper than H and after H, likely because this second implant destroys the H related complexes formed after H implantation, while these complexes are thought to be the precursors of platelets and blisters.…”
Section: Introductionmentioning
confidence: 99%
“…5,6,11,12,14 Other authors proposed that the second implant leads to the amorphization of the damaged zone preventing the formation of Si-H internal surfaces and, thus, of platelets. 13 On the other hand, several researchers have apparently shown that the fracture of silicon is possible and even more effective when hydrogen is implanted first. 2,3,12 In fact, all these works differ by the energies selected to implant the He and H ions.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Much knowledge has been acquired for the description of either the experimental results or the mechanisms involved. It has been commonly recognized that if the applied implantation fluence and thermal budget are sufficiently high, the surface exfoliation of the sample could occur at the depth corresponding to the range of H ions.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, several studies have demonstrated that sequential implantation of He and H ions could reduce both the total dose and the thermal budget necessary for the Si layer splitting. [10][11][12] Generally, it has been considered that the thin film separation process by light gas ion implantation proceeds through both chemical interactions (bond breaking, internal surface passivation) and physical interactions (gas coalescence, pressure and fracture) in the Si substrates. 10 However, the exact mechanisms involved are still not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, coimplantation of He and H ions into Si should be a good way to study the different role of the implanted gas ions in the film transfer process, the interaction between the two kinds of atoms, and the correlation between the defects created by H and/or He ions. Furthermore, recent studies [7][8][9] have revealed that He and H sequential implantation, i.e. successive implantation one species after the other, could lead to reduction of the splitting thermal budget as compared to H-only case at equivalent fluence.…”
Section: Introductionmentioning
confidence: 98%